Embracing the infidel : stories of Muslim migrants on the journey west - Yaghmaian, Behzad, 1953- (New York : Bantam Dell, 2006)
"An eye-opening account of a modern-day underground railroad that stretches from Istanbul to Paris and from London to New York City"--Cover.
Includes bibliographical references (p. [347]-348) and index.
Keywords: Refugees -- Abuse of -- Europe; Muslims -- Travel -- Europe; Refugees -- Crimes against -- Europe